Improving outcomes in patients with community-acquired pneumonia - Bewick, Thomas (2012)
Community-acquired pneumonia (CAP) is a leading cause of adult morbidity and mortality worldwide despite decades of effective antibiotics and vaccination initiatives. There have been no recent significant improvements in outcomes, including 30-day mortality. The bacterium Streptococcus pneumoniae is the most prevalent causative pathogen in CAP, being found in up to half of cases. In September 2006 a childhood pneumococcal vaccine (PCV-7) was introduced, leading to reductions in vaccine-type (VT) pneumococcal disease in infants, with possible additional benefits reported in adults. However, the effect that infant PCV-7 vaccination has on adult disease has to date been inadequately described in a small fraction of patients with invasive CAP, almost exclusively in populations in the US. These issues are explored fully in the literature review, encompassing chapters 1, 2 and 3.